Quality of different obturation techniques to fill perforating internal root resorption: a micro-computed tomographic study - Shaimaa Mohamed Abu El Sadat; Hooi Pin Chew; Alex Fok; Mohamed Mohamed Elashiry; Ahmed M. ElShenawy; Shehabeldin Saber (BMC, 2024)
Abstract Background This study aimed to assess the quality of various obturation techniques to fill perforation caused by internal root resorption using Micro-computed Tomography. Methods Cone-beam computed tomography images of a maxillary central incisor tooth with perforating internal resorptive defect were used to create a 3D printed model of the affected tooth. The replicas were divided into four groups based on the obturation technique used. The techniques included Group 1: a polydimethylsiloxane-based sealer (GuttaFlow-2) with gutta-percha. Group 2: same as Group 1 except for using a pre-mixed Bioceramic-based sealer (NeoSEALER Flo). Group 3: the defect was filled entirely using the NeoSealer Flo Bioceramic-based sealer. Group 4: the samples were obturated using the warm vertical compaction technique with a resin-based sealer (ADSeal). The resin models were then scanned a micro-computed scanner to evaluate the percentage of voids in each group. Results The results showed that NeoSEALER Flo groups had significantly the highest volume of voids while GuttaFlow-2 and warm vertical compaction groups had the lowest void volume. Conclusions GuttaFlow-2 and warm vertical compaction techniques performed best in filling the internal resorptive defect.